2021
DOI: 10.2991/absr.k.210408.060
|View full text |Cite
|
Sign up to set email alerts
|

Biochar Application on Spodosols Soils Promotes Higher Plant Growth and Survival Rate

Abstract: Interests in biochar applications for improving soil properties and fertility are increasing worldwide, and numerous production techniques, raw materials, and application options are now available. This research aimed to investigate the effects of biochar application on growth rate (height, stem diameter, leaf number, and survival) performance of Anthocephalus cadamba seedling planted on degraded Spodosols on bioassay trial in the nursery. Bioassay trial was carried out in Forestry Faculty of Mulawarman Univer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 63 publications
(68 reference statements)
1
5
0
Order By: Relevance
“…At the end of the observation period, only plants treated with M 3 media showed an average diameter significantly larger than another soil ameliorant (M1, M2) and (Table 3). Similar results were seen in the reduced high growth rate of Anthocephalus cadamba plants with greater biochar applications (25%v and 100%) [55]. This may be because microorganisms consuming volatile elements in biochar are responsible for nutrient immobilization [57,58].…”
Section: Survival Ratesupporting
confidence: 72%
See 2 more Smart Citations
“…At the end of the observation period, only plants treated with M 3 media showed an average diameter significantly larger than another soil ameliorant (M1, M2) and (Table 3). Similar results were seen in the reduced high growth rate of Anthocephalus cadamba plants with greater biochar applications (25%v and 100%) [55]. This may be because microorganisms consuming volatile elements in biochar are responsible for nutrient immobilization [57,58].…”
Section: Survival Ratesupporting
confidence: 72%
“…At the end of the study, Table 2 shows how many plants were still alive. Research in nursery shows a high survival rate (>90%) due to the provision of soil ameliorant that include biochar and other organic soil ameliorant [51][52][53][54][55]. However, the survival percentage in this trial was not particularly encouraging, despite being in the favorable category (50% -75%) [56].…”
Section: Survival Ratementioning
confidence: 66%
See 1 more Smart Citation
“…Native to Kalimantan, Anthocephalus cadamba is a quick-growing species called locally as "Kelapayan" and found in secondary forest, along riverbanks, swampy, and occasionally inundated places. For successful crop production on Spodosols, organic soil amendments and plant nutrients are required since it grows well on wet soils but poorly on deficient soils [11,12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Chitin, humic and fulvic acids, as well as other biopolymers found in liquid organic fertilizers, can also act as biostimulants on plants [18,19]. It has been demonstrated that adding biochar that has been enhanced with liquid organic fertilizer improves A. cadamba's growth performance in pot experiments with spodosols [8,13]. This study looked at the effects of applying biochar in combination with liquid organic fertilizers on the height growth of A. cadamba, which was grown in the field on degraded Spodosol soil.…”
Section: Introductionmentioning
confidence: 99%